Anomaloglossus meansi sp. n., a new Pantepui species of the Anomaloglossus beebei group (Anura, Aromobatidae) - Kok, Philippe J.R. (Zookeys, 2018)
Abstract. Recent extinctions and drastic population declines have been documented in the Guiana Shield endemic frog genus Anomaloglossus, hence the importance to resolve its alpha-taxonomy. Based on molecular phylogenies, the literature has long reported the occurrence of an undescribed species in the Pakaraima Mountains of Guyana in the Pantepui region. We here describe this new taxon and demonstrate that in addition to divergence at the molecular level the new species differs from congeners by a unique combination of morphological characters, notably a small size (maximum SVL in males 18.86 mm, maximum SVL in females 21.26 mm), Finger I = Finger II when fingers adpressed, Finger III swollen in breeding males, fringes on fingers absent, toes basally webbed but lacking fringes, in life presence of a thin dorsolateral stripe from tip of snout to tip of urostyle, and a black throat in preserved males (immaculate cream in females). Virtually nothing is known about the ecology of the new species. We suggest the new species to be considered as Data Deficient according to IUCN standards.